2022
DOI: 10.3390/pharmaceutics14081657
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro–In Vivo Relationship in Mini-Scale—Enabling Formulations of Corallopyronin A

Abstract: In vivo studies in mice provide a valuable model to test novel active pharmaceutical ingredients due to their low material need and the fact that mice are frequently used as a species for early efficacy models. However, preclinical in vitro evaluations of formulation principles in mice are still lacking. The development of novel in vitro and in silico models supported the preclinical formulation evaluation for the anti-infective corallopyronin A (CorA). To this end, CorA and solubility-enhanced amorphous solid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…By using the mesoporous silica formulation, it was possible to achieve increased solubility values for CorA tested in biorelevant media (FaSSIF: 0.835 ± 0.002 mg/mL; FeSSIF: 0.615 ± 0.031 mg/mL) [ 13 ]. Furthermore, in vitro dissolution indicated a fast dissolution rate.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…By using the mesoporous silica formulation, it was possible to achieve increased solubility values for CorA tested in biorelevant media (FaSSIF: 0.835 ± 0.002 mg/mL; FeSSIF: 0.615 ± 0.031 mg/mL) [ 13 ]. Furthermore, in vitro dissolution indicated a fast dissolution rate.…”
Section: Resultsmentioning
confidence: 99%
“…Data were analyzed using the Empower 3 software FR2, and quantified using an external reference standard. A solvent gradient was used comprising mobile phase A (acetonitrile/water 5/95 with 5 mM ammonium acetate and 40 μL acetic acid per liter) and mobile phase B (acetonitrile/water 95/5 with 5 mM ammonium acetate and 40 μL acetic acid per liter) with a gradient of 70% A/30% B to 20% A/80% B, added stepwise within 30 min at a flow rate of 0.3 mL/min [ 7 , 13 ]. For toxicokinetic analysis, the plasma concentrations of each dog were analyzed with the PK-Plus ® software (Simulations-Plus, Lancaster, CA, USA) using a non-compartmental model.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to the investigation of biodistribution towards tissues, organ concentrations were assessed in further organs after PO administration. Although in this study only low bioavailability was seen after PO administration compared to the IP and SC routes, recent studies have shown and predicted good bioavailability using a povidone-based amorphous solid dispersion method, paving the way to deploy this formulation for additional efficacy studies [ 23 , 29 ]. Whereas high rectum and pharynx concentrations of CorA might be attributed to the administration route, it was surprising to find CorA in the vaginal tract tissue as well as in tibia.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been proven that in terms of increasing solubility and dissolution, formulating ASDs is not only beneficial for crystalline drugs but also for poorly soluble drugs of amorphous nature [ 17 , 18 ]. Numerous ASDs have been demonstrated to improve dissolution properties by generating an aqueous supersaturated solution of the drug and stabilizing this state for a sufficient time, causing an increase in the bioavailability [ 15 , 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%